Development of a Heat-Treated Factor VIII/ von Willebrand Factor Concentrate Prepared from Heparinized Plasma - Palmer, D S; Ganz, P R; Perkins, H; Rosborough, D; Rock, G (Thrombosis and Haemostasis, 1990)
A high yield, intermediate purity factor VIII concentrate derived from heparinized plasma has been developed which can be heat-treated at 60 °C, 68 °C or 80 °C/72 h to permit inactivation of viral contaminants which may be present. After cold reprecipitation of the heparinized cryoprecipitate (CRC), the resolubilized CRC precipitate was adjusted to 25-30 mg/ml protein and pH 6.35 ± 0.1 and incubated for 1 h at 8 °C. After centrifugation to remove the precipitated fibrinogen and fibronectin, a factor VIII-rich supernatant can be recovered which contains > 500 units of VIII : C per liter of starting plasma (Method I product) at a purity of 1.5 U/mg protein. Adjusted to 50 mM glycine and pH 6.8, the product can be lyophilized and heat-treated at 60 °C/72 h without a significant loss of VIII :C activity. However, at 68 °C or 80 °C/72 h, temperatures now reported to be more effective in viral inactivation, the recoveries were reduced to 68 and 33% respectively. Significantly improved recoveries after heat-treatment (HT) at 68 °C or 80 °C/72 h were achieved if the 8 °C supernatant product was prepared by a modified procedure (Method II). This further reduces the fibrinogen content of the product while maintaining VIII : C yields > 500 U/l at a purity of 1.9 U/mg. When adjusted to 50 mM glycine and 1-2% (w/v) sucrose (pH 6.8), lyophilized and heat treated at 60 °C, 68 °C or 80 °C/72 h, the VIII :C recoveries of Method II product were 88-100%, 79-84% and 80-83% of pre-HT levels respectively. The yield of VIII : C was > 400 U/l at a purity of 1.6-1.4 U/mg at 1-2% (w/v) sucrose even after the severe heat-treatment at 80 °C. In addition, the von Willebrand factor multimers are similar in size and triplet pattern to those observed in routine cryoprecipitate preparations.